Sensory and autonomic function in the hands of patients with non-specific arm pain (NSAP) and asymptomatic office workers. - Greening, Jane; Lynn, Bruce; Leary, Rachel (PAIN, 2003)
Chronic pain in the upper limb associated with repetitive movements of the arm and hand is often seen in patients in the absence of specific pathology such as epicondylitis, carpal tunnel syndrome and tenosynovitis. This condition has been given many names and will be referred to here as non-specific arm pain (NSAP). Previous work has shown elevated vibration thresholds and reduced flare suggesting a neuropathic cause for this condition. In order to examine this further the present study has assessed functions that involve both large sensory nerve fibres (vibration) and small dorsal root fibres (flare) and sympathetic fibres (vasoconstriction). NSAP patients and also a group of office workers who intensively used display screen equipment but who did not have NSAP were also studied along with an age-matched control group. In the median innervated area of the hand we measured flare responses to iontophoresis of histamine (a sensory C-fibre effect), and sympathetic vasoconstrictor responses to ice stimulation over C7. To tie in with previous studies, vibration threshold over areas of the hand innervated by the median, ulnar and radial nerves was also evaluated. All measures were carried out over both hands in each subject. Significant differences from controls were found on all three measures for the NSAP patient group and on two measures for the office workers. Flare area was reduced by 33% in the patients and by 30% in the office workers. Reflex vasoconstriction was reduced by 20% in the patient group but was not altered in office worker group. Over the median innervated area on the hand, vibration threshold was elevated by 47% in the patients and by 21% in the office workers. These results confirm previous findings showing reduced function associated with both small and large sensory fibres in the NSAP patients and additionally, for the first time, demonstrate a functional change related to sympathetic fibres. Office workers demonstrate a similar but smaller trend for reduced nerve function associated with both small and large sensory fibre function, but had no change in the sympathetic reflex.